Teknik Hardening dan Aplikasi Paclobutrazol dalam Meningkatkan Vigor Planlet Anggrek Phalaenopsis amabilis - Aline Sisi Handini (JURNAL CITRA WIDYA EDUKASI, 2019)
Orchid is the one of largest flower species in the world, especially Phalaenopsis. This research was concern about post in vitro culture to improved planlets vigor. The objective of this study the Phalaenopsis orchid breeding process from tissue culture to enlargement to produce high-value crops. The result of observation showed that treatment H2P2 was the best. Statistic analysis showed that percentage survival rate 95%, lowest amount leaf, lowest height plant, lowest leaf width, lowest length leaf, and highest stomata density, founded in H2P2 treatment. So, can be used H2P2 treament as a recommendation for acclimatization for increasing the vigor planlets of Phalaenopsis amabilis.